Effects of Fertilization and Dry-Season Irrigation on Litterfall Dynamics and Decomposition Processes in Subtropical Eucalyptus Plantations - Kong, Jiejun; Lin, Yubiao; Huang, Feng; Liu, Wenquan; He, Qian; Su, Yan; Li, Jiyue; Wang, Guangyu; Qiu, Quan (Frontiers in Ecology and Evolution, 2022)
Nutrient management in Eucalyptus plantations is critical for wood production and sustainable development. Affected by the change of the spatiotemporal pattern of precipitation and plantation management, the biogeochemical mechanisms in Eucalyptus plantations remains not fully understood. The nutrient released from litterfall is an important input source of soil nutrient. We measured the seasonal production of various litterfall types and their nutrient release proportions in Eucalyptus urophylla × E. grandis plantations under compound fertilization, dry-season irrigation, and both. Our results showed that fertilization increased aboveground biomass and annual litterfall production (except leaf), and that the peak of litterfall production occurred in the rainy season. In the decomposition process, leaf decomposition rates were significantly higher than twig, which were mainly controlled by stoichiometric characteristics, followed by soil enzyme activity (β-glucosidase, urease, and polyphenol oxidase). Fertilization decreased litter carbon: nitrogen ratio and carbon: phosphorous ratio, and increased soil enzyme activities, which accelerates litter decomposition and nutrient release. Dry-season irrigation increased litter decomposition and only affected K release proportion by changing carbon: potassium ratio. Fertilization and dry-season irrigation accelerated nutrient cycle to enhance compensatory growth. These results help to comprehend the effects of forest management on litterfall dynamics and decomposition processes in Eucalyptus plantations with seasonal drought.